Integrating 21st Century Skill into EYL Class: A New Ideal Course Design and Planning for EYL Class - Erik yuda Pratama (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2016)
The economical, political, business and social challenges faced by the world today demand the 21st century skill-integrated as the main aspect that must be mastered by every child nowadays. This paper explores some important aspects related to integrating the 21 century skill into EYL class. Included in the discussion of this essay are the framework of 21st century skill, the 21st century curriculum, and designing appropriate syllabus for 21st century education suitable for EYL classroom, such as project-based syllabus and theme-based syllabus. This paper also describes several ICT media tool that can be used to promote our children 21st century skill, such as cartoon story maker (computer software) and kidblog (online blogging).